Improved meals service and reduced food waste and costs in medical institutions resulting from employment of a food service dietitian - a case study - Orit Yona; Rebecca Goldsmith; Ronit Endevelt (BMC, 2020)
Abstract Background A recurring problem in medical institutions is patients not always receiving food meeting their nutritional and medical needs. A proposed contributing factor is non- inclusion of dietitians in food service staff. Recently, positions for food service dietitians in hospitals were created. For the newly defined role of "Food Service Dietitian", comprehensive training courses were developed (70 dietitians participated). Objective To examine the impact of the addition of the role of a "Food Service Dietitian" in medical institutions on suitability of foods served, food costs and food waste. Methods A three years (2014-2017) national case study to examine the new role's impact was carried out, in 18 hospitals, nine of which employ a food service dietitian (intervention), and 9 without (control). The number of nutritional analyses of menus was checked, as was the extent of kitchen staff training, and how often night meals were served for all patients. Data were gathered regarding food costs and waste with respect to food distributed to staff and patients. Food costs savings and waste reduction were calculated, based on reduction in provision of unnecessary meals, at a cost of 18 NIS per day per meal. Results Kitchen staff training was carried out in all intervention institutions, and not in the controls. In most controls, nutritional analyses were not performed, whereas in the intervention hospitals, full analyses were performed and tailoring of menus to specific department requirements improved significantly. In most intervention hospitals, late night snacks were provided, this not being so in the controls. Total food cost savings of $229,569 per annum was seen in the six intervention hospitals, attributable to 4 factors: 1.Meals not delivered to fasting patients, or those receiving parenteral/enteral nutrition- cost savings of 328,500 NIS ($93,857)2.Better tailoring and monitoring of food delivered to the wards and staff (bread, cheese, milk etc)- annual cost savings of 235,000 NIS ($67,142) in the hospitals with a food service dietitian.3.Checking expiry dates of medical foods, and improved communication between the wards, the kitchen and the food distribution centers, has lessened food waste with savings of 5% from the medical food budget per annum of 40,000 NIS ($11,428).4.As a result of dietitian-performed nutritional analyses, tailoring of food provided according to the patient's medical and nutrition needs was improved. In one hospital, after re-evaluation of serve sizes in high protein diets, sizes were reduced while retaining adequacy, with immediate cost savings of 200,000 NIS ($57,142) per annum. Conclusions Implementation of the new role of Food Service Dietitian led to cost savings and significant improvements in adherence to the nutritional care plan.